2018
DOI: 10.3390/infrastructures3040058
|View full text |Cite
|
Sign up to set email alerts
|

Pavement Distress Detection Methods: A Review

Abstract: The road pavement conditions affect safety and comfort, traffic and travel times, vehicles operating cost, and emission levels. In order to optimize the road pavement management and guarantee satisfactory mobility conditions for all road users, the Pavement Management System (PMS) is an effective tool for the road manager. An effective PMS requires the availability of pavement distress data, the possibility of data maintenance and updating, in order to evaluate the best maintenance program. In the last decade,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(91 citation statements)
references
References 42 publications
0
87
0
4
Order By: Relevance
“…It is established that the first input data should reflect pavement conditions regarding surface and structure. The surface analysis refers to an evaluation of surface faults through a pavement distress survey [30], as well as the measurement of two performance indicators, which are the International Roughness Index (IRI) and the Rut Depth (RD). For its part, the structural analysis refers to assessing the structure of the pavement, considering the measurement of thicknesses, quality of the materials that make it up and load capacity.…”
Section: Input Datamentioning
confidence: 99%
“…It is established that the first input data should reflect pavement conditions regarding surface and structure. The surface analysis refers to an evaluation of surface faults through a pavement distress survey [30], as well as the measurement of two performance indicators, which are the International Roughness Index (IRI) and the Rut Depth (RD). For its part, the structural analysis refers to assessing the structure of the pavement, considering the measurement of thicknesses, quality of the materials that make it up and load capacity.…”
Section: Input Datamentioning
confidence: 99%
“…The critical and novel step in this process was the development of the distress categories for the model. Typically, pavement distresses can be broken down into four major categories namely: cracking, visco-plastic deformation, surface defects and other miscellaneous types [13]. The grouping is shown in Table 1.…”
Section: Data Annotationmentioning
confidence: 99%
“…The grouping is shown in Table 1. Of these categories, other studies have shown that there is a direct relationship between the impact each distress has upon safety and comfort per level of severity [13]. Based on this each distress has an impact based on the severity of the occurring distress.…”
Section: Data Annotationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Highway and especially in airport the evaluation of road pavement performance is essential for effective maintenance design engineering (Barbarella et al, 2018;Barbarella et al, 2017). The research is oriented towards the study of survey methods in order to obtain increased safety, higher data collection speed, higher accuracy data, and minimising traffic interference (Ragnoli et al, 2018;Yen et al, 2011). The 3D laser scanner technology has high potential to collect reliable road profiles, moreover it is possible to visualize the pavement roughness covering the entire pavement (Chang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%